Economic, environmental, and social sustainability of Alternate Wetting and Drying irrigation for rice in northern Italy - Gharsallah, Olfa; Rienzner, Michele; Mayer, Alice; Tkachenko, Darya; Corsi, Stefano; Vuciterna, Rina; Romani, Marco; Ricciardelli, Andrea; Cadei, Elisa; Trevisan, Marco; Lamastra, Lucrezia; Tediosi, Alice; et al. (Frontiers in Water, 2023)
Italy is Europe’s leading rice producer, with over half of total production almost totally concen-trated in the north-western part of the Padana plain. In this area, rice irrigation has traditionally been carried out by wet seeding and continuous flooding. The replacement of this technique with the dry seeding and delayed flooding in the last 15 years brought economic benefits to farmers but also strong impacts to the water resource system of the area, characterised by a strong interaction between irrigation and shallow aquifer levels. Wet seeding and alternate wetting and drying (AWD) could be seen as an alternative irrigation strategy; however, its environmental, economic and social sustainability must be investigated before supporting the dissemination of this ‘water-saving’ irrigation technique over the territory in cooperation with decision-makers and water re-source managers. In this paper, the results of an experimental activity carried out in a platform established in the main Italian rice district to compare three irrigation strategies (wet seeding and traditional flood-ing - WFL, dry seeding and delayed flooding from around the 3-leaf stage - DFL, wet seeding and alternated wetting and drying from the tillering stage - AWD) and data further provided by the farm holder (agronomic inputs and economic costs for the three options) were used to assess their economic and environmental sustainability through an assessment procedure based on quantitative indicators. Interviews with rice growers in the area were used to identify barriers to the adoption of AWD and subsequently propose ways to overcome them. AWD proved to be economically viable and to reduce the irrigation need in the peak month (June) without significantly affecting rice yield or quality (cadmium and arsenic content in rice grain). Additionally, it guarantees the recharging of the phreatic aquifer in the first period of the irriga-tion season, while reducing the methane (CH4) emissions, facing another significant environmen-tal challenge of rice cultivation. Rice growers in the region stated their willingness to adopt AWD, although they would need technical, technological and financial support. The assessment proce-dure adopted in this paper proved to be effective for comparing rice irrigation techniques and is available for further studies.